Konsep Jihad Salahuddin Al- Ayyuby Menurut Pandangan Ibn Al-Athir Dan Al-Isfahani - Kalupae, Abdulasi (2014)
Salahuddin al-Ayyuby was an Islamic leading warrior of the Muslim world. He successfully liberated Jerusalem and became the founder of government in Egypt and Syria. The Great Victory was achieved by the defeat of the Crusaders in the Battle of Hittin. He also unified the ranks of Muslim in Egypt, Syria, Yaman, Sudan and Asia Minor. In addition, he successfully unified the Islamic people in Egypt, Syria, Yemen, Sudan, and Asia Minor during 6-12 century AD. Moreover, he could achieve and build human well-being irrespective of race and religion in particular to defend the honor of Islam. This study used qualitative methods through the library as well as three main sources that is al-Kamil fi al-Tarikh composed by Ibn al-Athir, al-Barq al-Syami and al- Fath al-Qusi fi al-Fath al- Qudsi, both composed by al-Isfahani and other manuscripts used as a reinforcement to study the concept of Jihad performed by Salahuddin al-Ayyuby. Furthermore, the comparative method was also used to compare similar perspectives in five aspects, namely jihad against the Crusaders, unification of the ranks of Muslims, the liberation of Jerusalem military administration and peace. However, there are different perspectives in term of the management of society and politics. The different perspectives and views are mainly due to the fact that they are working in different situation. These similarities and differences show that the concept of Salahuddin’s jihad was not only focused on the aspect of the war alone. Yet, it covers the whole aspect of life.